2019
DOI: 10.2118/190435-pa
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Liquid Injectivity in Surfactant-Alternating-Gas Foam Enhanced Oil Recovery

Abstract: Surfactant alternating gas (SAG) is often the injection strategy used for injecting foam into a reservoir. However, liquid injectivity can be very poor in SAG, and fracturing of the well can occur. Coreflood studies of liquid injectivity directly following foam injection have been reported. We conducted a series of coreflood experiments to study liquid injectivity under conditions more like those near an injection well in a SAG process in the field (i.e., after a period of gas injection). Our previous experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 35 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…Water saturation inside the finger increases and finally reaches approximately 0.9, indicating that gas trapped within the liquid finger has dissolved into liquid or been displaced. In our previous study (Gong et al 2019b), we showed that the rise in liquid saturation within the finger and the progress of the finger through the core roughly correspond to the rate of gas dissolution expected for N 2 under our experimental conditions. This dissolution causes a huge rise in water relative permeability within the finger and subsequent diversion of virtually all water through the 4.…”
Section: Experiments and Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Water saturation inside the finger increases and finally reaches approximately 0.9, indicating that gas trapped within the liquid finger has dissolved into liquid or been displaced. In our previous study (Gong et al 2019b), we showed that the rise in liquid saturation within the finger and the progress of the finger through the core roughly correspond to the rate of gas dissolution expected for N 2 under our experimental conditions. This dissolution causes a huge rise in water relative permeability within the finger and subsequent diversion of virtually all water through the 4.…”
Section: Experiments and Resultssupporting
confidence: 77%
“…In our earlier study (Gong et al 2019b), we referred to a fingering process followed by gas dissolution into the finger. An analysis of the CT images in Figs.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations